AB0848-HPR Promotion of health-enhancing physical activity – a comparative study between italy and sweden. (23rd January 2014) - Brodin, N.; Hurkmans, E.; Di Matteo, L.; Nava, T.; VlietVlieland, T.; Opava, C. H.
Abstract : Background: Many people with rheumatoid arthritis (RA) are physically inactive despite proven health benefits. Effective methods for physical activity (PA) promotion have been developed, but little is known about their use among health professionals in rheumatology. A previous study described factors related to promotion of PA, defined as any bodily movement resulting in energy expenditure, among Dutch health professionals. The results indicated that a majority agrees that PA is important and regularly recommend it to their patients, but do feel a need for additional education in the area. Objectives: The objective of our study was to describe and compare the attitudes of Italian and Swedish health professionals towards PA, to what extent they promote PA among their patients with RA, their perceived competencies to promote PA and their related educational needs. Methods: A questionnaire was sent to 1402 Italian and 837 Swedish health professionals (rheumatologists, nurse specialists and physiotherapists). The 23-item questionnaire on PA promotion, originally developed for the Dutch study (1 ), was translated into Italian and Swedish according to standard procedures. Results: The response rate was 25 % in Italy and 29 % in Sweden. Sixty-four percent of the respondents were female, mean age was 45, 6 years and mean experience within rheumatology 12, 8 years. Ninety-six percent of Italian health professionals and 99 % of those in Sweden agreed that PA is an important health goal for patients with RA and regularly advised their patients to engage in it. Public health recommendations for moderate-intensity PA were found attainable in patients with RA by 89 % and 96 % and were used by 90 % and 91% of those in Italy and Sweden respectively. On average, respondents in Italy and Sweden rated their competency to promote PA as 7, 1 and 5, 6 out of 10 respectively, and 89 % and 69 % of them expressed a need for additional education. Conclusions: Our results indicated similar attitudes to PA as an important health goal, higher rating of this as attainable for people with RA and more than twice as high use of public health recommendations compared to their Dutch peers. The only major differences between Italy and Sweden concerned the lower perceived competency, but less expressed need for education found among the Swedish respondents compared to those in Italy. The response rate of our study was less than half of that in the Dutch study and, in addition to threatening the external validity of the study, might indicate less interest in PA promotion among Italian and Swedish health professionals compared to those in the Netherlands. However, assuming that the responders were mainly those considering PA a suitable intervention for their patients, this would only strengthen the case for attitude changes and raised competencies for physical activity promotion among health professionals in rheumatology. References: Hurkmans EJ et al. Promoting physical activity in patients with rheumatoid arthritis: rheumatologists' and health professionals' practice and educational needs. Clin Rheumatol 2011;30:1603–1609 Acknowledgements: This study was funded by 'the EULAR Health Professionals Research Grant 2012'. Disclosure of Interest: None Declared